Role of Corporate Social Responsibility in the Relationship between Strategy Analysis and Organizational Performance of Sugar Companies in Western Kenya - Ayub, Shitseswa; Onditi, Arvinlucy; Nyagol, Michael (International Journal of Multidisciplinary and Current Research, 2017)
This study investigates the role of corporate social responsibility in catalyzing the relationship between strategy analysis and organizational performance. The design is descriptive and correlational survey of employee perceptions of strategy analysis and it association with organization performance. Findings reveal that indeed strategy analysis relate well to sugar firm performance in the presence of social investments in the communities they operate in. when CSR activities are not incorporated in the planning for better performance, then results are not likely to be good. Therefore it is necessary for corporate managers to integrate CSR programs in their strategy plans in order to leverage firm performance.
Keywords: Strategy analysis; Organization performance; Corporate social responsibility